Roemer 20 Years Later: When a Classical Health-System Typology Meets Market-Oriented Reforms - Bourque, Melanie; Farrah, Jean-Simon (Revue Gouvernance / Governance Review)

(untitled) (Centre d’études en gouvernance de l’Université d’Ottawa, 2012)
In 1990, Roemer came up with a very influential health system typology. From his vast study, emerged three types of health care systems: nationalized, mandated and entrepreneurial. Health care systems are not static; slow changes and reforms somewhat alter values and goals on which those systems were initially established. It is fair to say, then, that over the last two decades, health care reformers have adopted a market-oriented governance model that blends new public management (NPM) and managed competition reforms in the provision of health care services to transform supply- and demand-side actors into “responsibilized” customers, payers or providers. These transformations beg the question as to whether we are witnessing a radical redefinition of health care systems through the implementation of market-oriented governance. We propose to add the evolution of market-oriented health reforms in five case studies to Milton Roemer’s typology of health systems. In light of our findings, we will wrap up the analysis with an assessment of the usefulness of Roemer’s classification for social scientists to grasp the evolution of health systems over the past 20 years, and more importantly, to analyze the current state of these health care systems after years of market-oriented reforms.